2010
DOI: 10.1073/pnas.0911184107
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional changes to hippocampal theta–gamma comodulation predict memory for recent spatial episodes

Abstract: Episodic memory requires the hippocampus, which is thought to bind cortical inputs into conjunctive codes. Local field potentials (LFPs) reflect dendritic and synaptic oscillations whose temporal structure may coordinate cellular mechanisms of plasticity and memory. We now report that single-trial spatial memory performance in rats was predicted by the power comodulation of theta (4-10 Hz) and low gamma (30-50 Hz) rhythms in the hippocampus. Theta-gamma comodulation (TGC) was prominent during successful memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
215
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(228 citation statements)
references
References 39 publications
9
215
2
2
Order By: Relevance
“…In the rat hippocampus, there is a remarkable low-frequency activity, the well-known ''theta rhythm.'' It has been reported that the theta rhythm modulates gamma oscillations (Bragin et al 1995a;Tort et al 2008;Colgin et al 2009;Belluscio et al 2012) and their CFC alters depending on the running speed (Chen et al 2011;Ahmed and Mehta 2012) and the behavioral performance (Tort et al 2009;Shirvalkar et al 2010). Here we particularly focused on the CFC during a delay period, which several studies have suggested to require the involvement of hippocampus for successful task performance (Ainge et al 2007;Pastalkova et al 2008;Takahashi et al 2009a, b;MacDonald et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the rat hippocampus, there is a remarkable low-frequency activity, the well-known ''theta rhythm.'' It has been reported that the theta rhythm modulates gamma oscillations (Bragin et al 1995a;Tort et al 2008;Colgin et al 2009;Belluscio et al 2012) and their CFC alters depending on the running speed (Chen et al 2011;Ahmed and Mehta 2012) and the behavioral performance (Tort et al 2009;Shirvalkar et al 2010). Here we particularly focused on the CFC during a delay period, which several studies have suggested to require the involvement of hippocampus for successful task performance (Ainge et al 2007;Pastalkova et al 2008;Takahashi et al 2009a, b;MacDonald et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This could allow for the simultaneous implementation of multiple coding schemes for memory items, stored in both a sequential and nonsequential context (Senior et al, 2008). Recent data from LFP recordings from both rat and human hippocampus provide evidence for a functional role of thetaegamma PAC in mnemonic processing (Axmacher et al, 2010;Shirvalkar et al, 2010;Tort et al, 2009), but these hippocampal models and examples also reflect a broader hypothesis of PAC function: hierarchies of inter-locked oscillatory frequencies allow ensembles of anatomically localized neurons co-active on short timescales (i.e. within higher-frequency cycles, e.g.…”
Section: Cross-frequency Coupling In Neuronal Datamentioning
confidence: 99%
“…Researchers have employed amplitude-phase comodulation as well as phase-phase comodulation. The form commonly referenced in EEG literature is amplitude-amplitude power comodulation and is generally reported as a correlation coefficient (Shirvalkar, Rapp, & Shapiro, 2010). Collura (2008) noted the similarity between the equation for comodulation and Pearson's correlation while pointing out that the comodulation measurements are ''amplitudes across time.''…”
mentioning
confidence: 99%